Cooperative spectrum sharing protocol with selective relaying system - Han, Yang. (2013)
In this paper, we propose a two-phase protocol based on cooperative relaying for a secondary system to achieve spectrum access along with a selective relaying primary system. The primary system comprises of a transmitter-receiver pair PT-PR and M relays Ri, i G {1,2,⋯ , M}. The secondary system is a multi-user system with N transmitters Ri, i ϵ {M +1, M + 2, ⋯ , M + N } which intend to communicate with a common receiver SR. In the proposed protocol, terminals Ri, i ϵ M1 = {1, 2, ⋯ , M + Q} are designated as possible candidates for assisting the primary system while the remaining secondary transmitters Ri', i' ϵ M2 = {M + Q + 1, M + Q + 2, ⋯ ,M + N} are chosen as possible candidates for secondary spectrum access, where 0 ≤ Q ≤ N. The relaying terminal Rp, p ϵ M1 which achieves the request target rate for the primary system and has the best channel to PR, is first selected from M1 to serve as a decode-and-forward (DF) relay for the primary system. With the cooperation of Rp, the primary system is able to tolerate some interference lower than a certain threshold in the relaying phase, without degrading its outage performance. The secondary transmitter Rs, s ϵ M2 which satisfies this interference constraint and optimizes the outage performance for the secondary system, is then selected from M2 to access the spectrum band simultaneously when Rp is relaying the primary signal. Analytical and simulation results confirm the efficiency of the proposed spectrum sharing protocol. We show that there exists an optimal value for Q and both primary and secondary systems are able to achieve better outage performance with increasing N.